Nutrient intake in adolescents with risky eating behavior - Vasquez Pérez, Cristina Janeth; Torres Mata, Denisse Adriana; Valbuena Gregorio, Edith; Márquez Ibarra, Adriana Alejandra (Horizonte Sanitario, 2024)
Objective: Compare nutrient intake based on categories of disordered eating behaviors in adolescents. Materials and methods: The present study has a non-experimental cross-sectional analytical design, with a quantitative approach. Sampling was carried out at convenience. The brief questionnaire of risky eating behaviors used by Padrós-Blázquez et al. was used, and weight and height were determined to form the body mass index. The 24-hour reminder dietary survey was also applied to calculate the percentage of adequacy and determine nutrient intake, the percentages of adequacy (%AD) were calculated, and the nutrient ranges were taken according to the Recommended Dietary Allowances (RDA), for sugar the recommendation of the Nutrition Committee of the European Society of Pediatric Gastroenterology, Hepatology and Nutrition was used. An overadequate AD was considered when the %AD was >110%, adequate with a range of 110 - 90%, low <90%. Results: A combined prevalence of risky eating behaviors of 37.88% was found, with medium and high risk (25.76% and 12.12% respectively). A significant difference was found in the intake of vitamin A, ascorbic acid, iron, and folate among the categories, being higher in the low-risk group compared to the medium and high-risk groups. Additionally, overadequate %ADs were found for sugar, energy, protein, potassium, sodium, and carbohydrates, while the lowest %ADs were for folate, fiber, and phosphorus. Conclusions: Nutrient intake differs according to the REB category, and key micronutrients for adolescence are involved in low intake, which can cause negative health effects. Keywords: Nutrients; Eating behavior; Adolescents.